A compendium of objective questions in civil engineering - Sharma, A Krishna (UniversitiesPress, 2014)
A compendium of objective questions in civil engineering / Sharma, A Krishna. -- Kolkata: UniversitiesPress, 2014 153.94624 V462 No. of Copies : 1